Extrinsic rewards and intrinsic motives: Standard and behavioral approaches to agency and labor markets - James B. Rebitzer; Lowell J. Taylor (Institute for the Study of Labor (IZA), 2010)
Employers structure pay and employment relationships to mitigate agency problems. A large literature in economics documents how the resolution of these problems shapes personnel policies and labor markets. For the most part, the study of agency in employment relationships relies on highly stylized assumptions regarding human motivation, e.g., that employees seek to earn as much money as possible with minimal effort. In this essay, we explore the consequences of introducing behavioral complexity and realism into models of agency within organizations. Specifically, we assess the insights gained by allowing employees to be guided by such motivations as the desire to compare favorably to others, the aspiration to contribute to intrinsically worthwhile goals, and the inclination to reciprocate generosity or exact retribution for perceived wrongs. More provocatively, from the standpoint of standard economics, we also consider the possibility that people are driven, in ways that may be opaque even to themselves, by the desire to earn social esteem or to shape and reinforce identity.
Keywords: D2; J0; M5; 330; agency; motivation; employment relationships; behavioral economics; Arbeitsverhältnis; Leistungsanreiz; Prinzipal-Agent-Theorie; Motivation; Arbeitsverhalten; Verhaltensökonomik; Theorie